Agricultural Development Bank Reform: The Case of The Bank for Agriculture and Agricultural Cooperatives (BAAC), Thailand - Klaus Maurer; Shyam Khadka; Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2000)
The Bank for Agriculture and Agricultural Cooperatives (BAAC) in Thailand has gone through four major phases of reform: 1966-74, laying the foundation for individual lending to farmers through joint liability groups; 1975-87, expanding its lending operations through access to commercial bank and donor funds and consolidating its operations by reducing loan channeling through cooperatives; 1988-96, striving for viability and self-reliance, under conditions of controlled interest rates, through savings mobilization, improved loan recovery and increased staff productivity; since 1997, adjusting to prudential regulation by the central bank and diversifying into non-agricultural lending. The result of gradual reform has been the largest outreach by any Agricultural Development Bank: 88% of farm households in Thailand, combined with institutional viability.
Keywords: 330; Landwirtschaftsbank; Thailand; Bank for Agriculture and Agricultural Cooperatives; Kruṅ deb